Development of Educandy Platform as an Educational Game to Improve Arabic Language Learning Achievement - Rezi, Melisa; Quintana, Jacob; Dominic, Walker; Darius, Liu (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
Game-based learning is certainly very favored by students, especially nowadays games in learning do not need to be done in the classroom using a cellphone. One application that can be developed to improve student achievement is the Educandy platform. The purpose of this research is to develop the Educandy platform as a learning media in improving Arabic language learning achievement. The method used in this research is research and development method with ADDIE model. The results of this study indicate that the Educandy platform is able to improve student achievement so that students are happy in learning Arabic. The conclusion of this study can be seen that the use of the Educandy platform as an educational game in learning Arabic can support the learning and teaching process. The limitation of this research is that researchers only make Arabic language games at the junior high school level so that the game cannot be developed as a whole, for that the researcher hopes that the next researcher can do the same research and be practiced at boarding schools where there is more knowledge about Arabic lessons.